Balancing Industry Needs against Global Competitiveness: A Challenge for the Australian Vegetable Industry. (September 2013) - Ariyawardana, Anoma; Collins, Ray
The Australian vegetable industry is a significant contributor to the national economy and regional development, generating employment opportunities both on-farm and along the farm-to-market chain. However, the high cost structure of the industry has negatively affected its competitiveness and production is declining, resulting in the relocation of some processing facilities to other countries and increasing imports. These outcomes threaten the future viability of the industry and impact on food-safety-conscious consumers in Australia. Thus, the aim of this paper is to review policy issues along the producer to consumer chain and discuss how key stakeholders could be affected by alternative policy options. The current context of the vegetable industry shows that Australia faces a challenge to find appropriate policy solutions to achieve global competitiveness and secure the interests of its stakeholders while at the same time adopting a market-based policy approach to its food industry.